Hypothermia causes platelet activation in the human spleen. Issue 205 (September 2021) - Horioka, Kie; Tanaka, Hiroki; Okaba, Keisuke; Yamada, Shinnosuke; Ishii, Namiko; Motomura, Ayumi; Inoue, Hiroyuki; Alkass, Kanar; Druid, Henrik; Yajima, Daisuke
Abstract: Background: Accidental hypothermia results in various dysfunctions in the human body. Additionally, coagulation disorder can lead to a life-threatening condition. We previously demonstrated that platelets stored in the spleen were activated and thus triggered coagulation disorder in a mouse model of hypothermia. In the present study, we wanted to investigate if this phenomenon in mice also occurs in humans as a reaction to hypothermia. Methods: We analyzed splenic tissue collected from 22 deceased subjects who have died from hypothermia. These samples were compared with 22 control cases not exposed to cold environment. We performed immunohistochemical staining for CD61 (a marker of all platelets) and CD62P (a marker of activated platelets). We also evaluated the morphology of platelets in the spleen with scanning electron microscopy. Results: Immunohistochemical analysis revealed no significant changes in the amounts of CD61-positive platelets between the hypothermia and control cases. However, the hypothermia cases contained abundant CD62P-positive platelets compared with those of the control cases. Immunohistochemical analysis also revealed that the activated platelets formed aggregates and adhered to splenic sinusoidal endothelial cells in the hypothermia cases. However, we observed no significant fibrin formation around the activated platelets. Conclusions: Hypothermia resulted in splenic platelet activation, which may be used as a postmortem marker of hypothermia. The release of activated platelets from the spleen into to circulation upon rewarming may promote coagulation disturbances. Highlights: Low temperature inhibits postmortem changes in humans, and hypothermia can preserve vital signs in patients. Immunohistochemistry was used to analyze platelets taken from hypothermic human spleens. Hypothermia activates platelets in the spleen; this activation can be a marker of hypothermia. This phenomenon is consistent with our previous report in murine hypothermia model. Splenic platelet activation may have important biological significance in hypothermia.